Esaform 2021 2021
DOI: 10.25518/esaform21.4298
|View full text |Cite
|
Sign up to set email alerts
|

Further development of a numerical method for analyzing the load capacity of clinched joints in versatile process chains

Abstract: In many branches of production, components using large number of joints are combined together to make complex structures. The use of mechanical joining techniques offers the possibility to join structures with a wide range of material/geometry configurations. Due to changing in material properties during the production of formed parts, the robustness of the joint must be guaranteed. In this regard, a numerical method has been developed to predict the geometrical properties of the joint as a function of pre-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…It should be noted that for the mixed steel-aluminum joint, the material combinations AJ2 and CJ2 cannot be investigated because the clinched joints exhibit neck fractures. This phenomenon has already been investigated and described in detail by Bielak et al 14…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…It should be noted that for the mixed steel-aluminum joint, the material combinations AJ2 and CJ2 cannot be investigated because the clinched joints exhibit neck fractures. This phenomenon has already been investigated and described in detail by Bielak et al 14…”
Section: Resultsmentioning
confidence: 67%
“…There is a negative correlation between the neck thickness and the interlock, whereby the sheet thickness reduction has a stronger influence on the neck thickness and the interlock than the pre-strengthening due to the pre-strain. This method has been further developed by Bielak et al 14 to numerically investigate the influence of defined pre-deformation of the joining parts on the load-bearing behavior under shear tensile loading. Quality-relevant parameters of clinched joints as well as the maximum transmittable force under shear load were determined.…”
Section: Introductionmentioning
confidence: 99%
“…3 Rotation mapping from a 2D rotational symmetric to a 3D model hardening caused by the joining process of the material. The procedure is described in more detail in [18].…”
Section: D-modell Rotation and Strain/stress Mappingmentioning
confidence: 99%
“…for body in white applications. 1 A widely used joining process is clinching, which does not require any additional auxiliary joining element. 2 In addition to the initial semifinished product properties, each of these operations influences the resulting properties of the parts and thus the subsequent manufacturing steps.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such joining processes are highly sensitive to changes in the properties of the components to be joined. 4 In Bielak et al 1 it was shown that preforming has an influence on the joinability and that this affects the load-bearing capacity. To ensure a consistent joint quality and thus component quality, the alteration of the component properties must be taken into account in the design of clinched joints.…”
Section: Introductionmentioning
confidence: 99%